Suicide in the City Do Characteristics of Place Really Influence Risk? - Denney, Justin T (Social science quarterly, 2015)
OBJECTIVE: This article investigates the role of social context on individual suicide mortality with attention paid to the possibility that contextual effects are simply the sum of individual characteristics associated with suicide